Tolerance deviations of the exhaust system regarding to template manufacturing errors with application of 6-Sigma - Ferreira, Filipe Queiroz Soares; e Chaves, Matheus Stephen Nascimento; Magalhães, Raphael Ramos (International Journal of Advanced Engineering Research and Science, 2021)
This article aims to explain the negative impact of tolerance deviations in exhaust systems due to template manufacturing errors. It also attempts to present the application of Six sigma as a solution for the issue since it helps to correct those errors of the templates. Six Sigma is a quality management methodology, that when applied correctly, helps to achieve greater standardization, which in turn improves the quality of exhaust system. It also ends up positively impacting work culture and increasing customer satisfaction. The article is based on the comparison between estimated productivity and estimated losses. Due to confidentiality reasons all data was estimated. The research also focused on 6-Sigma solution method for the automotive industry. The results obtained proved the benefits of the application of Six Sigma.